Accounting the effects of WTO accession on trade-embodied emissions: Evidence from China. (15th December 2016) - Liu, Zhengyan; Song, Peng; Mao, Xianqiang
Abstract: The indicators of the 'emissions embodied in exports', the 'balance of emissions embodied in trade' and the 'net emissions contributed by trade' are used to measure the trade-embodied environmental impacts from various angles. A counterfactual scenario of "without WTO accession" is formed as the comparative baseline with the support of a dynamic computable general equilibrium model. Then the difference between factual and counterfactual scenarios is worked out to reflect the impact of China's WTO accession on emissions embodied in trade. According to the present study, WTO accession produced a measureable 'increment of the emissions embodied in exports' through exports expansion, which slightly intensified environmental stress in China. If considering the difference in emissions embodied in exports and imports, then the 'difference of the balance of emissions embodied in trade between factual and counterfactual scenarios' indicate that China has suffered more local emissions than its trade partners after its WTO-accession; if considering the offset effect of imports embodied emissions to domestic emissions, then the 'difference of the net emissions contributed by trade between factual and counterfactual scenarios' indicate that WTO accession had a trivial effect on aggregating trade-embodied emissions. The study results suggest that China should continue pushing for trade liberalization and at the same time, reduce the adverse effects on the environment by reducing its total emissions intensity of domestic production and optimizing trade structure. Graphical abstract: Highlights: Factual and counter-factual scenarios are constructed to show WTO accession impacts. EIO and CGE models are employed to calculate trade embodied emissions. China's WTO-accession produced measureable increment of embodied emission. WTO accession worsened the net emissions exporter position of China. Adverse effects are acceptable if considering the offset effect of imports.